Long Palindromic Sequences Induce Double-Strand Breaks during Meiosis in Yeast - Nasar, Farooq (American Society for Microbiology, 2000)
Inverted-repeated or palindromic sequences have been found to occur in both prokaryotic and eukaryotic genomes. Such repeated sequences are usually short and present at several functionally important regions in the genome. However, long palindromic sequences are rare and are a major source of genomic instability. The palindrome-mediated genomic instability is believed to be due to cruciform or hairpin formation and subsequent cleavage of this structure by structure-specific nucleases. Here we present both genetic and physical evidence that long palindromic sequences (>50 bp) generate double-strand breaks (DSBs) at a high frequency during meiosis in the yeast Saccharomyces cerevisiae. The palindrome-mediated DSB formation depends on the primary sequence of the inverted repeat and the location and length of the repeated units. The DSB formation at the palindrome requires all of the gene products that are known to be responsible for DSB formation at the normal meiosis-specific sites. Since DSBs are initiators of nearly all meiotic recombination events, most of the palindrome-induced breaks appear to be repaired by homologous recombination. Our results suggest that short palindromic sequences are highly stable in vivo. In contrast, long palindromic sequences make the genome unstable by inducing DSBs and such sequences are usually removed from the genome by homologous recombination events.